2022
DOI: 10.1080/24733938.2022.2114603
|View full text |Cite
|
Sign up to set email alerts
|

A multi-club analysis of the locomotor training characteristics of elite female soccer players

Abstract: Objective: Quantifying differences in locomotor characteristics of training between two competition levels and between training days within elite female soccer players. Methods: Foot-mounted inertial measurement unit (Playermaker) data were collected from 293 players from three Women's Super League (WSL; n = 76) and eight Women's Championship (WC; n = 217) teams over a 28-week period. Data were analysed using partial least squares correlation analysis to identify relative variable importance and linear mixed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recently, inertial measurement devices (IMU) have been designed (Edwards et al, 2019), which, placed in the soccer player´s boot, can represent a low-cost option that improves the task of monitoring the soccer player´s TL and PL. Some studies have shown the ability to monitor both TL and PL in English professional teams over an extended period of the season, analyzing the tasks of training sessions with male and female players (Barrett et al, 2020;Marris et al, 2021;Lewis et al, 2022;Myhill et al, 2022). Previous studies on monitoring TL and PL in soccer players have primarily focused on official matches or without considering TL (Barnes et al, 2014;Suarez-Arrones et al, 2015;Akenhead and Nassis, 2016), this is where we find a gap in information and knowledge, which P.S.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Recently, inertial measurement devices (IMU) have been designed (Edwards et al, 2019), which, placed in the soccer player´s boot, can represent a low-cost option that improves the task of monitoring the soccer player´s TL and PL. Some studies have shown the ability to monitor both TL and PL in English professional teams over an extended period of the season, analyzing the tasks of training sessions with male and female players (Barrett et al, 2020;Marris et al, 2021;Lewis et al, 2022;Myhill et al, 2022). Previous studies on monitoring TL and PL in soccer players have primarily focused on official matches or without considering TL (Barnes et al, 2014;Suarez-Arrones et al, 2015;Akenhead and Nassis, 2016), this is where we find a gap in information and knowledge, which P.S.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Recently, inertial measurement devices (IMU) have been designed ( Edwards et al, 2019 ), which, placed in the soccer player´s boot, can represent a low-cost option that improves the task of monitoring the soccer player´s TL and PL. Some studies have shown the ability to monitor both TL and PL in English professional teams over an extended period of the season, analyzing the tasks of training sessions with male and female players ( Barrett et al, 2020 ; Marris et al, 2021 ; Lewis et al, 2022 ; Myhill et al, 2022 ). Previous studies on monitoring TL and PL in soccer players have primarily focused on official matches or without considering TL ( Barnes et al, 2014 ; Suarez-Arrones et al, 2015 ; Akenhead and Nassis, 2016 ), this is where we find a gap in information and knowledge, which P.S.…”
Section: Introductionmentioning
confidence: 99%